Histopathological Study and Immunohistochemistry of Mediastinal Masses of Anterior Compartment - Vemuluri, Mounica; Philipose, Thoppil Reba (Annals of Pathology and Laboratory Medicine, 2023)
Background: The mediastinum is the mid portion of the thoracic cavity, further divided into the anterior, middle, and posterior mediastinum. The numerous organs within the mediastinum make it prone to the development of various lesions. About half of all mediastinal masses occur in the anterior compartment. The most common are thymoma, lymphoma and mature teratoma. An accurate histopathological diagnosis is required for the management of mediastinal lesions. Methods: This is a 2-year prospective study conducted in the Department of Pathology on Biopsies and Resected Specimens of Anterior Mediastinal Masses (AMM) in a tertiary care hospital from September2020-September2022. Sections were studied after staining with hematoxylin and eosin(H&E). Immunohistochemical (IHC) stains were done wherever required. Result: The present study included 58 cases of AMM. The age of the patients ranged from 2-77 years. Males constituted 68.90 % of cases. The male-to-female ratio was 5:2.2. Cough was the most common presenting symptom. Thymic pathology was detected in 56.8% of cases, of which thymoma is the most common. Thymoma presented with Myasthenia Gravis (M.G.) in 2 cases. Lymphoma constituted 12% of cases. Metastatic carcinoma in 12%, Extragonadal Germ Cell Tumor (EGCT) in 8.6% and lymphangioma in 3.4% cases. Lipoma, sarcoidosis and myofibroblastic tumor each constitute 1.72% cases. Conclusion: The present study describes the various lesions of the anterior compartment.